2018
DOI: 10.1080/16066359.2018.1457654
|View full text |Cite
|
Sign up to set email alerts
|

How physicians professional socialisation and social technologies may affect colleagues in substance use disorders

Abstract: Often, discussions of physicians' substance use (both licit and illicit) are framed in quantitative terms. The present article provides a complimentary qualitative and posthumanist perspective on substance use challenges illuminated through in-depth interviews with substance use disorder (SUD) recovered physicians' about their experiences with substance use and SUD within their work culture. SUD recovered physicians' experiences include descriptions of fears about being revealed as a substance user, self-medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…When coding out empirical material, this perceived clash between professionals´ training in care and health support and dealing with substance-using older citizens, including accepting their autonomy, was a recurring theme. Such dilemmas concerning substance use privacy and professionalism mirrored patterns found in studies of other health professionals namely physicians (Sørensen et al, 2016;Sørensen, 2019). Having trained as both nurses and SOSU-assistants and SOSU-helpers, these professionals are trained to support healthy livingyet they may need to compromise this over and over again in order to respect privacy rights.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…When coding out empirical material, this perceived clash between professionals´ training in care and health support and dealing with substance-using older citizens, including accepting their autonomy, was a recurring theme. Such dilemmas concerning substance use privacy and professionalism mirrored patterns found in studies of other health professionals namely physicians (Sørensen et al, 2016;Sørensen, 2019). Having trained as both nurses and SOSU-assistants and SOSU-helpers, these professionals are trained to support healthy livingyet they may need to compromise this over and over again in order to respect privacy rights.…”
mentioning
confidence: 84%
“…[…] If they don't want to accept help first of all, because they're comfortable in their misuse, or that thing where you see a life falling apart in misuse […] That you can't give them the help they need, because either they don't want it, or because the right services aren't there, and they don't fit into what we can offer. Sørensen, 2019). In that sense, the elderly care sector is characterized by a duality between 1) providing 'correct' health care and treatment as well as nudging citizens towards more healthy living and 2) respecting citizens´ autonomy even in cases of a conduct that is potentially highly damaging to their health and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Substance use, particularly alcohol use, is often regarded as private and is accordingly tabooed as a non-intrusive area (Bach et al, in press;Sørensen, 2019;Sørensen et al, 2016).…”
Section: Dominating Logics In Danish Elderly Care Servicesmentioning
confidence: 99%
“…“Rather blood alcohol levels than pills” [DA: hellere promiller end piller ] was the slogan of Thyra Frank, former Minister of the Elderly (and former manager of a privately run nursing home, which had a more relaxed approach to alcohol than public nursing homes), meaning that the life of the elderly should be joyful rather than marked by caution as well as a belief that moderate drinking could be gentler than medication (ibid.). Substance use, particularly alcohol use, is often regarded as private and is accordingly tabooed as a non-intrusive area ( Bach et al, in press ; Sørensen, 2019 ; Sørensen et al, 2016 ).…”
Section: Dominating Logics In Danish Elderly Care Servicesmentioning
confidence: 99%
“…Besides a tendency of minimization and denial of early symptoms [27], impaired physicians indicated that they feel ashamed and that they fear accessing mental healthcare [24,25]. Their fear includes being stigmatized as a 'patient' or 'addict' and losing their professional confidentiality and career perspective [24][25][26]28]. Minimization and denial of early symptoms and the authority to prescribe drugs subsequently impede identification of SUD in physicians [29].…”
Section: Introductionmentioning
confidence: 99%